Pós-humano e além-do-humano: uma abordagem do transumanismo através do conceito de Niilismo no pensamento de Friedrich Nietzsche. - Soares, Breno Dutra Serafim (2018)
This doctoral thesis has the fundamental objective of criticizing transhumanism from the concept of nihilism in the work of Friedrich W. Nietzsche. To do so, part of a controversy generated by some thinkers who, from the 90's of the twentieth century, began to establish a relationship between the german thinker and the transhumanist movement. Some theorists of this movement have established a fundamental connection between the transhumanist movement and Nietzsche, assuming that this thinker would provide with his philosophy a more robust foundation for ideas fundamental to the movement. Our aim is therefore to determine the validity of such observations, whether they were accurately established or not, through a critique of Nietzsche's attachment to the transhumanist movement from the concept of nihilism, which is fundamental in the philosopher's thinking. In order to achieve this general objective, we start from the elucidation of the concept of nihilism in Nietzsche's work, from the thematization of the concept in its origin and roots in the context of Western culture. After this, we carry out the same course with transhumanist thinking, trying to establish the fundamental characteristics of this current of Western thought, as well as determining the means by which transhumanism seeks to assert itself, spreading in the context of thought and culture of this early 20th century. Still in the second chapter, we seek to establish how the transhumanist thinkers seek to realize this connection between Nietzsche's thought and the doctrine they defend. In a third moment, we seek to defend our hypothesis that transhumanism identifies, according to the nietzschean view, as a kind of nihilism. To this end, we make considerations about the use of science by the german philosopher. First, for Nietzsche, science has a positive role because if functions as a mechanism to free the human being from the ideal of truth as a consolation, typical of metaphysics and the judeo-christian religion. However, in a second moment, science reveals itself as heir to Western nihilism because if adopts the ideal of conservation and promotion of humanity, whether this organic or postorganic “humanity”. Finally, we make use of Nietzsche's concept of the overhuman to establish a confrontation with transhumanist thinking, whose objective is the creation of the post-human, a concept that the adherents of this doctrine compare to the nietzschean overhuman.